"Applying Content Analysis and Thematic Analysis in Identifying the Sustainable Supply Chain Practices - Case Study of TOYOTA company " - اسماء جنحاني (جامعة الوادي university of eloued, 2024)
"أصبح مفهوم الاستدامة في سلسلة التوريد يحظى مؤخرا باهتمام كبير في الأوساط الأكاديمية وسرعان ما انتقل ذلك الإهتمام إلى مجال الصناعات سنوات قليلة بعد ذلك, كتحصيل حاصل للترابط بينهما, الشيء الذي دفع بالدول والاقتصاديين إلى الالتزام بالاستدامة. في هذا الصدد، تكون الشركات مسؤولة عن الجوانب الاجتماعية والبيئية والاقتصادية لأنشطتها، والمعروفة باسم المحصلة الثلاثية. يدرس هذا البحث ممارسات سلسلة التوريد المستدامة في صناعة تصنيع السيارات لهذه المناقشة من خلال تقديم رؤية جديدة لاستكشاف هذا الرأي. التركيز الرئيسي لهذا البحث كان للتحقيق في وجهات نظر شركة TOYOTA COMPANY للتحكم في الاستدامة أثناء تنفيذ استراتيجياتها في سلسلة التوريد. لذلك ، أجرينا تحليلًا موضوعيًا ، وهي طريقة قوية تسعى جاهدة لفهم سياسات سلسلة التوريد المستدامة في TOYOTA company وذلك خلال الفترة الزمنية من سبتمبر 2022 إلى ماي 2023 باستخدام برنامج التحليل النوعي NVivo14. تكشف النتائج أن سلسلة التوريد المستدامة في شركة تويوتا تحظى بأكبر قدر من الاهتمام بالاقتصاد الدائري. تعكس النتائج علاقة قوية بين ممارسات سلسلة التوريد المستدامة المتقدمة والاقتصاد الدائري. ستخلص هذه الدراسة إلى أن شركة TOYOTA تعتبر الاقتصاد الدائري وسيلة لتحسين ممارسات سلسلة التوريد المستدامة المتقدمة. يؤكد البحث أن دمج مبادئ الاقتصاد الدائري ضمن إدارة سلسلة التوريد المستدامة يمكن أن يوفر مزايا واضحة من وجهة نظر اقتصادية واجتماعية وبيئية " "The concept sustainability in the supply chain has received significant attention in academia and industries in few years later, which obliges the governments and economists to adhere sustainability. In this regard, businesses are responsible for their activities’ social, environmental and economic aspects, named triple bottom line. This paper studies sustainable supply chain practices in the Automotive manufacturing industry to this discussion by providing new insight into exploring that view. The main focus of this research is to investigate TOYOTA company points of view to control the sustainability during implementation its supply chain strategies. Therefore, we conducted a thematic analysis, a powerful method that strives to understand policies sustainable supply chain in TOYOTA company from September 2022 to May 2023 using NVivo qualitative software. The findings reveal that sustainable supply chain in TOYOTA company have the most significant attention with circular economy. The findings reflect strong relation between advanced sustainable supply chain practices and circular economy. This study will conclude that TOYOTA company consider circular economy as a means to improve their advanced sustainable supply chain practices. The research confirms that the integration of circular economy principles within sustainable supply chain management can provide clear advantages from an economic, social and environmental point of view "
Keywords: الاستدامة، سلسلة التوريد، صناعة السيارات، الاقتصاد الدائري، تويوتا Sustainability; Supply chain; Automotive manufacturing industry; Circular economy; TOYOTA company.